Effect of Lime Addition Methods on Performance Related Properties of Asphalt Concrete Mixture - Amjad Hamd Khalil Albayati, Prof. Dr.; Ahmad Mahir Mohammed (Journal of Engineering, 2016)
In the recent years, some of the newly constructed asphalt concrete pavements in Baghdad as well as other cities across Iraq showed premature failures with consequential negative impact on both roadway safety and economy. Frequently, load associated mode of failure (rutting and fatigue) as well as, occasionally, moisture damage in some poorly drained sections are the main failure types found in those newly constructed road.